The need for adequate argumentation for the protection of biotic community - Klimski, Marcin (Studia Ecologiae et Bioethicae, 2016)
The changing state and quality of the environment is now taken for granted by communities living in many distant parts of the world. It is felt more and more intensely that disadvantageous interference in the natural environment will sooner or later have an impact on the biotic community, including humans themselves. However, the problem has not yet been so clearly accentuated, so as to prevent the effects, which often become irreversible. Environmental ethics is one of the scientific disciplines which has attempted to find proper arguments for the protection of the biotic community, as well as to enhance the feelings of responsibility and care for the socio-natural environment. Among the ethical ideas which are developed in this context, the holistic view presents the broadest scope of human moral responsibility for the natural world. Such an approach is considered to have originated in the writings of the American researcher, Aldo Leopold. His ideas and great determination have become well known to those who were not indifferent to the issues of respect for the environment and environmental protection. The article outlines the possibility to incorporate arguments based on the thought of Aldo Leopold, in the process of environmental education, whose aim is the protection of biotic community.